The (un)suitability of fair-value accounting in emerging economies: the case of Vietnam. Issue 2 (3rd June 2019) - Nguyen, Lisa-Uyen
Abstract : Purpose: This study aims to explore the suitability and challenges of implementing fair value accounting (FVA) in Vietnam, an emerging/transitioning economy. While such implementation would enable convergence with International Financial Reporting Standards, standard setters and auditors have raised practical concerns about its adoption. Design/methodology/approach: This qualitative study uses semi-structured interviews with regulators and auditors, together with an analysis of two fraud cases that illustrate the business environment in Vietnam. Public, private and capture theories guide the analysis. Findings: The business and institutional environment in Vietnam creates several impediments to FVA being effectively implemented and transparently applied. Given the major challenges identified regarding the infrastructure necessary for this valuation system, the premature adoption of FVA may become a catalyst for corporate misconduct. Research limitations/implications: The findings are derived from data aggregated from two fraud cases and interviews, and as such, the results may not be generalisable to other settings. However, these findings may inform future research, particularly after the Ministry of Finance provides further guidance on the use of FVA in Vietnam. Practical implications: A timely and critical examination of the challenges of implementing FVA in a transitioning economy is provided, and the two fraud cases reveal the complexities of the business environment in Vietnam. Originality/value: This research gives voice to the tensions that developing countries are confronting as they seek to balance external pressures with internal constraints. The introduction of an assemblage of three theoretical lenses enables insights into contemporary issues associated with applying FVA in such settings.